Information technology. International standardized profiles TB, TC, TD and TE. Connection-mode transport service over connection-mode network service. Definition of profile TC53, provision of the OSI connection-mode transport service using the OSI connection-mode network service in an end system attached to a token ring LAN Part 14, (15th July 1995) - British Standards Institution,
No abstract available